2020
DOI: 10.1128/jcm.00798-20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Abbott ID Now and Abbott m2000 Methods for the Detection of SARS-CoV-2 from Nasopharyngeal and Nasal Swabs from Symptomatic Patients

Abstract: The ID NOW COVID-19 (IDNCOV) assay performed on the ID Now Instrument (Abbott Diagnostics, Scarborough, Inc. Scarborough, ME) is a rapid diagnostic test that can be performed in a point of care setting equivalent to CLIA waived testing.…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
170
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(187 citation statements)
references
References 0 publications
16
170
0
1
Order By: Relevance
“…Nasal swabs directly tested on the ID NOW assay had 48% positive agreement compared to the CRS, whereas Simplexa had 88%, m2000 had 96% and Xpert had 100% positive agreement (Table 1). While the deficit in positive percent agreement (PPA) seen in ID NOW test results is consistent with other early release studies in the scientific literature ((1–4, 79)), it is surprising given the ID NOW’s LOD claim of 125 genome equivalents/mL, which is similar to the 100 copies/mL claimed by the m2000 method, 250 copies/mL claimed by Xpress and 242 copies/mL claimed by Simplexa. To clarify this apparent discrepancy, a direct assessment of the analytic sensitivity of all assays in this comparison was performed utilizing dilutions of inactivated SARS-CoV-2 whole virus (ZeptoMetrix).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Nasal swabs directly tested on the ID NOW assay had 48% positive agreement compared to the CRS, whereas Simplexa had 88%, m2000 had 96% and Xpert had 100% positive agreement (Table 1). While the deficit in positive percent agreement (PPA) seen in ID NOW test results is consistent with other early release studies in the scientific literature ((1–4, 79)), it is surprising given the ID NOW’s LOD claim of 125 genome equivalents/mL, which is similar to the 100 copies/mL claimed by the m2000 method, 250 copies/mL claimed by Xpress and 242 copies/mL claimed by Simplexa. To clarify this apparent discrepancy, a direct assessment of the analytic sensitivity of all assays in this comparison was performed utilizing dilutions of inactivated SARS-CoV-2 whole virus (ZeptoMetrix).…”
Section: Resultssupporting
confidence: 74%
“…In the absence of clinical trials and a gold standard for COVID-19 diagnosis, the clinical performance of SARS-CoV-2 assays is unclear. Anecdotal claims of poor NAAT performance exist in the lay press, and limited studies have shown variable performance of rapid POC tests (19). As a surrogate for a gold standard, a composite reference standard (CRS) can be used to determine the consensus of comparable assays and identify outlier assays in terms of clinical performance (10).…”
Section: Introductionmentioning
confidence: 99%
“…32 Another study determined that the POC test (ID NOW) was less sensitive compared with the traditional RT-PCR assay. 33 Furthermore, to prepare for the upcoming flu season, diagnostic assays that can simultaneously detect for SARS-CoV-2 and the influenza virus to determine the cause of infection will be important to clinical treatment, infection control, and community mitigation efforts.…”
Section: Assay Performance and Limitationsmentioning
confidence: 99%
“…The diagnostic test, capable of delivering results in 5 to 13 minutes. 3 Because of the novelty of this virus as well as the recent introduction of these tests into the health care market, there are little comparison data in any emergency setting to measure performance. Given the criticality of maximizing accuracy and getting some quantification of a false-negative rate, the aim of this study was to evaluate the agreement of the diagnostic performance of the ID NOW COVID-19 with the Abbott m2000 real-time PCR, the institutional presumed reference standard, for SARS-CoV-2 in patients presenting to an urban ED.…”
mentioning
confidence: 99%
“…This was supported by prior in-house testing, validation data, and recent literature. 3 If ID NOW returned negative, the paired NP sample was then tested on the m2000 instrument for concordance. During the study period, results were used to determine patient disease status in standard care.…”
mentioning
confidence: 99%